ICTV Virus Taxonomy Profile: Mymonaviridae 2022. (18th November 2022) - Jiāng, Dàohóng; Ayllón, María A.; Marzano, Shin-Yi L.; Kondō, Hideki; Turina, Massimo; ,
Abstract : Typical members of the family Mymonaviridae produce filamentous, enveloped virions containing a single molecule of linear, negative-sense RNA of about about 10 kb, but some may not produce any virions. The family includes several genera, some with multiple species. Mymonavirids usually infect filamentous fungi, but a few have been identified associated with insects, oomycetes or plants. At least one virus, Sclerotinia sclerotiorum negative-stranded RNA virus 1, induces hypovirulence in its fungal host. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Mymonaviridae, which is available at ictv.global/report/mymonaviridae .